The Oscillometric Pulse Wave Analysis Is Useful in Evaluating the Arterial Stiffness of Obese Children with Relevant Cardiometabolic Risks - Mihuta, Monica Simina; Paul, Corina; Borlea, Andreea; Cepeha, Cristina Mihaela; Velea, Iulian Puiu; Mozos, Ioana; Stoian, Dana (Journal of clinical medicine, 2022)
Early detection of all complications of childhood obesity is imperative in order to minimize effects. Obesity causes vascular disruptions, including early increased arterial stiffness and high blood pressure. This study’s aim is to assess the reliability of pulse wave analysis (PWA) in obese children and how additional risk factors influence the evaluated parameters. We analyzed 55 children aged 6–18 years old by measuring their pulse wave velocity (PWV), augmentation index (AIx), peripheral blood pressure (SBP, DBP), heart rate, central blood pressure (cSBP, cDBP) and central pulse pressure (cPP). We used the oscillometric IEM Mobil-O-Graph and performed a single-point brachial measurement. The subjects were divided into two groups: obese (n = 30) and normal-weight (n = 25) and were clinically and anamnestically assessed. BMI and waist circumference are significantly correlated to higher values for PWV, SBP, DBP, cSBP, and cDBP. Weight significantly predicts PWV, SBP, DBP and cPP. The risk factors that significantly influence the PWA and BP values are: a cardiometabolically risky pregnancy (higher PWV, AIx, SBP), active and passive smoking (higher PWV, SBP, cSBP, cDBP), sleep deprivation (higher PWV, SBP, cSBP) and sedentariness (higher PWV, AIx, peripheral and central BP). We conclude that obese children with specific additional cardiometabolic risk factors present increased arterial stiffness and higher blood pressure values.